The Self-efficacy of Primary School Teachers in Teaching Mathematics: A Comparative Research on Teacher Training Program Products - Rahayu, Lina Puspitaning; Sartono, E. Kus Eddy; Miftakhuddin, Miftakhuddin (Mimbar Sekolah Dasar, 2019)
This research aims at comparing the self-efficacy of primary school (SD – Sekolah Dasar) teachers who have taken teacher training program (PPG – Program Pelatihan Guru) on mathematics teaching and those who have not, which was seen from the personal belief sub-factors in teaching mathematics and the expected mathematics teaching outcomes. This research employed quantitative method with comparative research type to 198 samples. The data were analysed through T-test using SPSS. The result showed that there was no significant self-efficiency differences between primary school teachers who have taken PPG on mathematics teaching and those who have not. The results of this research indicated that self-efficacy was an important variable in pedagogical competence as it could influence the way teachers manage the classroom to attain maximum students’ achievement.